PmrC (EptA) and CptA Negatively Affect Outer Membrane Vesicle Production in Citrobacter rodentium - Sinha, Anshul (J Bacteriol, 2019)
Outer membrane vesicles (OMVs) are naturally produced by Gram-negative bacteria by a bulging of the outer membrane (OM) and subsequent release into the environment. By serving as vehicles for various cargos, including proteins, nucleic acids and small metabolites, OMVs are central to interbacterial interactions and both symbiotic and pathogenic host bacterial interactions. However, despite their importance, the mechanism of OMV formation remains unclear. Recent evidence indicates that covalent modifications of lipopolysaccharides (LPS) influence OMV biogenesis. Several enteric bacteria modify LPS with phosphoethanolamine (pEtN) using the iron-regulated PmrC (EptA) and CptA pEtN transferases. In wild-type Citrobacter rodentium, the presence of increasing subtoxic concentrations of iron was found to stimulate OMV production 4- to 9-fold above baseline. C. rodentium uses the two-component system PmrAB to sense and adapt to environmental iron. Compared to the wild type, the C. rodentium ΔpmrAB strain exhibited heightened OMV production at similar iron concentrations. PmrAB regulates transcription of pmrC (also known as eptA) and cptA. OMV production in strains lacking either pmrC (eptA) or cptA was similarly increased in comparison to that of the wild type. Importantly, plasmid complementation of C. rodentium strains with either pmrC (eptA) or cptA resulted in a drastic inhibition of OMV production. Finally, we showed that β-lactamase and CroP, two enzymes found in the C. rodentium periplasm and outer membrane (OM), respectively, are associated with OMVs. These data suggest a novel mechanism by which C. rodentium and possibly other Gram-negative bacteria can negatively affect OMV production through the PmrAB-regulated genes pmrC (eptA) and cptA. IMPORTANCE Although OMVs secreted by Gram-negative bacteria fulfill multiple functions, the molecular mechanism of OMV biogenesis remains ill defined. Our group has previously shown that PmrC (also known as EptA) and CptA maintain OM integrity and provide resistance to iron toxicity and antibiotics in the murine pathogen Citrobacter rodentium. In several enteric bacteria, these proteins modify the lipid A and core regions of lipopolysaccharide with phosphoethanolamine moieties. Here, we show that these proteins also repress OMV production in response to environmental iron in C. rodentium. These data support the emerging understanding that lipopolysaccharide modifications are important regulators of OMV biogenesis in Gram-negative bacteria.